Factors of adventivization of roadside plant communities in the south of the Russian Black Sea Region - V.A. Chadaeva; R.H. Pshegusov (Учёные записки Казанского университета: Серия Естественные науки)
Roadside plant communities in the south of the Russian Black Sea region are characterized by relatively high adventivization and low invasibility. In these communities, the adventivization has been rapidly progressing due to the high abundance and competitiveness of invasive species in the region. The total projective cover of codominant species (from invasive species) is also important: an increase in the value of this parameter reduces the levels of adventivization and invasibility. On the Black Sea coast, the highest concentration of roadside plant communities with relatively more competitive invasive species is observed between the Mzymta and Shakhe Rivers, i.e., under the conditions of moderately humid subtropical climate. From the coast to the mountains, the communities with invasive species occur along the flat river valleys (Terrain Ruggedness Index with the probability of finding these communities exceeds 50%).